Comparative transcriptome analysis of brain and gonad reveals reproduction-related miRNAs in the giant prawn, Macrobrachium rosenbergii - Xia, Jiao; Liu, Dong; Zhou, Wenzong; Yi, Shaokui; Wang, Xinhai; Li, Beilei; Jawad, Muhammad; Xu, Haijing; Gui, Lang; Li, Mingyou (Frontiers in Genetics, 2022)
Macrobrachium rosenbergii (M. rosenbergii), as a species of common prawn, is a delicacy that is consumed all over the world. MicroRNAs (miRNAs) participate in the reproductive process by regulating the expression of target genes. However, research focusing on miRNA regulation during gonadal development in M. rosenbergii received very little attention. To explore the association between miRNA and reproduction, we performed RNA sequencing (RNA-seq) on brain and gonad organs in male and female M. rosenbergii. A total of 494 miRNAs were obtained in RNA-seq, including 31 and 59 differentially expressed (DE) miRNAs in the brain and gonads, respectively. Furthermore, 9 DE miRNAs were randomly selected from the brain and gonads, and qRT-PCR was performed to evaluate the results of RNA-seq. Interestingly, dpu-miR-133 was found highly expressed in the male brain and testis, but poorly expressed in the female brain, ovary, and other organs. Analysis of dpu-miR-133 by Targetscan and MiRanda predicted to target 5-HT1. In addition, the dual-luciferase reporter assay manifested that dpu-miR-133 can combine with 5-HT1. Overall, our research work provides basic data for further study into the role of miRNA-mediated regulation of brain, gonad, and reproductive development of study M. rosenbergii.